Use of ammonium-enriched skim latex serum to compost rubber biomass wastes and its effect on planting Brassica alboglabra - Jutarut Iewkittayakorn,; Juntima Chungsiriporn,; Prukraya Pongyeela, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ammonium-enriched skim latex serum - used for absorption of contaminating ammonia gas - when composted with other rubber tree wastes, is promising as a good compost. The objective of this research was to utilize ammonium-enriched skim latex serum (S) as a raw composting ingredient after being combined with para sawdust (W1) and para rubber leaves (W2). Several ratios of S, W1 and W2 were experimented in a 15L composting vessel to determine the most effective compost. The best ratio was found to be 3:1:3 by weight at 12-day retention. The modified 30 L composting reactor employed with the derived optimum mixing conditions yielded N, P and K of 2.40, 1.51 and 14.84 %w/w. The growth of Brassica alboglabra after application of this compost combined with a chemical fertilizer generated the highest fresh weight (4.48 g/plant). Thus, compost from these wastes could be used as a fertilizer and logically should contribute to cost saving of waste disposal.